Visualization Experiment of Bubble Coalescence in a Narrow Vertical Rectangular Channel - Ren, Tingting; Zhu, Zhiqiang; Zhang, Rui; Shi, Jiangwu; Yan, Changqi (Frontiers in Energy Research, 2020)
Visualization experiments were carried out and sliding bubble coalescence behaviors were observed for subcooled flow boiling in a narrow rectangular channel. The results show that the consecutive coalescence process is composed of four steps based on the bubble morphological change: approach, fusion, adjustment and stabilization, in which the more important are the fusion and adjustment of the bubble. Bubble always slides along the heating surface and does not lift off in coalescence process. Bubble diameter and sliding velocity increase first, then decrease and finally stabilize. Bubble shape also oscillates from an irregular ellipse to a stable circle. In addition, a new small bubble may be induced in the coalescence process.